Rancang Bangun Aplikasi E-Voting Pemilihan Boulo Vuyu Berbasis Android Di Dinas Pariwisata Kab. BolMong Utara - Syaifuddin Syaifuddin; Hamka Witri Kamase (Fakultas Teknik Universitas Muhammadiyah Bengkulu, 2022)
The election of Putra and Putri Daerah is one of the activities held every year by the Tourism Office, including in Bolaang Mongondow Utara. If in Jakarta elections like this are called Abang Noni Jakarta elections, then in Bolaang Mongondow Regency, it is called Boulo Vuyu election. Bolaang Mongondow District Tourism Office is one part of the Republik Indonesia tourism ministry in the area, tasked with providing services to local and local communities. One of the activities is often organized by the Tourism Office of Bolaang Mongondow Utara Regency, which is the election activity of Boulo Vuyu. The activity can encourage and motivate people to preserve, develop, and promote regional arts and culture in the community, especially in the younger generation. The research aims to design an e-voting design application that can select the favourite Boulo Vuyu, using waterfall research methods, then generate the design of e-voting applications that can solve the problems. The study results concluded that the Application could facilitate the committee in evaluating the number of participants who follow boulo vuyu and the people who conducted the selection of the favourite Boulo Vuyu.